024 Handheld electronic device use in patient care; the emergency department patient perspective. Issue 12 (21st November 2019) - Tilbury, Nicholas; Johnson, Graham; Byrne, Carol; Churchman, Adam; Shergill, Maleasha; Rusk, Zoe; Tabner, Andrew
Abstract : What is already known?: Smartphones have an increasingly important role to play in the delivery of healthcare, especially in the acute setting. Little is known regarding patient perceptions of this development. Why is this study important?: Staff are concerned that patients have a negative perception of their use; this concern may present a barrier to optimal use despite the existing evidence of their benefits. What does this study add?: Our study describes patient, carer and relative attitudes towards staff use of smartphones within an emergency department. The majority of respondents trust staff to use their devices appropriately and are supportive of the use of this evolving technology in a healthcare setting. A cross-sectional survey of emergency department service users in a single department at all times of day and on all days of the week. Surveys were administered by medical students; all eligible individuals in the department during a data collection period were approached. Results: A total of 438 participants successfully completed the survey with a response rate of 98%. Only 2% of those who observed staff using HEDs during their emergency department visit thought that they were being used for non-clinical purposes. 340 (72%) agreed that staff should be allowed to use HEDs in the workplace. Concerns expressed by participants included devices being used for non-clinical purposes and data security. The main suggestion by participants was that the purpose of the HEDs should be explained to patients to avoid misinterpretation. Conclusion: Our study suggests that the majority of individuals attending the emergency department have no concerns regarding the use of HEDs by clinical staff, and that many of the concerns raised could be addressed with adequate patient information and clear governance.